Transdisciplinary Challenges in Landscape Ecology and Restoration Ecology - An Anthology - Naveh, Zev (Landscape Series,, 2007)
Capitalizing on forty years of intensive ecological studies, this anthology presents a collection of widely dispersed major publications on theoretical and practical Mediterranean, global environmental and landscape issues. These range from Mediterranean ecosystems and vegetation types in California and Israel, to the significance of fire in the evolution of cultural Mediterranean landscapes in the Pleistocene and Early Holocene with special reference to Mt. Carmel; and from the development of Tanzania Masailand, a sociological and ecological challenge to multifunctional, self-organizing biosphere landscapes and the future of our Total Human Ecosystem. Each chapter features a comprehensive study of ecological and landscape issues, synthesized in the introduction, and woven with autobiographical experiences. The concluding chapter calls for a transdisciplinary shift in all environmental scientific fields and particularly in landscape and restoration ecology, to cope with the complex, closely interwoven ecological, socio-economical, political and cultural crises facing human society during the present crucial transition from the industrial to the post-industrial, global information age. Updating and broadening the scope of the groundbreaking Springer book on Landscape Theory and Applications by the author and Lieberman (1994), this is a unique transdisciplinary attempt based on advanced systems complexity theories, which link the natural and human sciences. It will be of value for all those dealing with land and landscape study in the broadest sense as academic scientists, researchers and scholars, professionals and practitioners and students.